2013
DOI: 10.4322/rca.2013.038
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de sementes de canafístula via calor úmido

Abstract: RESUMO: O tratamento térmico é utilizado, frequentemente, para superação de dormência em sementes florestais; porém, este ainda possui potencial para controle de micro-organismos veiculados pelas sementes. O objetivo deste trabalho foi avaliar os efeitos do tratamento térmico via calor úmido na qualidade fisiológica e na sanidade das sementes de canafístula-Peltophorum dubium. O delineamento experimental utilizado foi inteiramente casualizado, com quatro repetições. As sementes, coletadas em 2006, são provenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…The presence of pathogens can reduce the physiological quality of the seeds; the integration of tests for the health and physiological quality of the seeds is therefore recommended (LAZAROTTO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of pathogens can reduce the physiological quality of the seeds; the integration of tests for the health and physiological quality of the seeds is therefore recommended (LAZAROTTO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…pathogens incidents in the oilseeds of jatropha (Jatropha curcas L.), confirming the results of the present work. Lazarotto et al (2013) verified that the thermotherapic treatments via humid heat (80 ºC for 0; 5; 10; 15 and 20 min) were not efficient to prevent the infestation of phytopathogens on the seeds of cassia fistula without affecting negatively its physiological quality. Nevertheless, Cunha et al (2017) concluded that the thermotherapy via humid heat at 60 ºC for until 18 min reduces the incidence of phytopathogens in squash seeds without damage in their physiological quality.…”
Section: Resultsmentioning
confidence: 82%
“…(Marchi et al, 2008), Spondias mombin (Spondias mombin L.) (Brito et al, 2008), canafistula (Peltophorum dubium Spreng.) (Lazarotto et al, 2013), cumaru (Amburana cearensis A.C. Smith) (Oliveira et al, 2011), beans (Phaseolus vulgaris L.) (Estefani, Miranda Filho, & Uesugi, 2007), castor oil plant (Ricinus communis L.) (Marroni et al, 2009), passion fruit (Passiflora suberosa L.) (Marostega et al, 2015), maize (Zea mays L.) (Coutinho et al, 2007), tomato (Solanum lycopersicum L.) Carmo et al (2004) Braga et al (2010), among others, without damage to the physiological quality, offering an alternative to the use of chemical products, commonly used in the seeds treatment. Oliveira et al (2011) highlight that this form of seeds treatment is viable for the pathogens control, without environmental damage, because it does not use pollutants and it does not emit residues.…”
Section: Introductionmentioning
confidence: 99%
“…Taub. (Lazarotto et al, 2013) e Dimorphandra mollis Benth. (Honório et al, 2010) (Machado, 2000), sendo considerados danos irreversíveis que podem reduzir tanto a germinação (Coutinho et al, 2007) quanto o potencial de armazenamento das sementes (Marcos Filho, 2015).…”
Section: Resultsunclassified